CLINICAL AND HEMATOLOGICAL EVALUATION OF THE ANTITHROMBOTIC CARDIOPULMONARY BYPASS FOR THE OPERATIONS OF THE THORACIC DESCENDING AORTIC ANEURYSMS - FUJIKI, T.; ARIMURA, Y.; KOKUBO, J.; EGAMI, J.; IDE, H.; TONARI, K.; IKEDA, K.; KOISHIZAWA, T.; HONDA, K.; HAYASHI, N.; SUDO, K.; WATANABE, Y.; et al. (Jinko Zoki, 1995)
Consecutive 8 patients involving true or dissecting aneurysms of the thoracic descending aorta or thoracoabdominal aorta were operated upon under the partial cardiopulmonary bypass using the antithrombotic coated device. The system is consisted of Maxima membrane oxygenator, Bio-Medicus centrifugal pump, and Medtronic percutaneous thin wall cannulae. These were all coated with Carmeda Bioactive Surace. Polyvinyl tube was coated with Biomate. The administration of systemic heparin was determined by ACT of around 200 seconds. All patients were tolerated operations well and alive. No thromboembolic accident, bleeding tendency, nor organ failure including renal failure were observed postoperatively in all patients. The analysis of blood platelets, coagulation, and fibrinolysis system revealed minimal fluctuation of the values. In conclusion, this system of anti thrombotic circuit is safe and preferable for thoracic descending or thoraco-abdominal aneurysm operations.